Mudanza - Portabella, Pere 1927-; Prandi, Elisabeth ca. 20. Jh (2021)
"The film records the removal of furniture and objects from the building, leaving visitors able to move freely amongst its empty spaces and a silence charged with feeling." [amazon.com]
Original: Spanien 2008
Bildformat 2.00:1
Keywords: Leere -- Motiv; Huerta de San Vicente -- Granada